Diversity and specificity of sap‐feeding herbivores and their parasitoids on Australian fig trees. Issue 2 (21st November 2016) - Fromont, Caroline; DeGabriel, Jane L.; Riegler, Markus; Cook, James M.
Abstract: The ecology, diversity, and parasitoid complex of plant–sap feeding insects of the family Homotomidae (Hemiptera: Psylloidea) specialised on fig trees ( Ficus ) have so far received little research attention. They are ecologically important, however, as occasional outbreaks of the homotomid Mycopsylla fici may cause complete defoliation of its host plant, the Moreton Bay fig ( Ficus macrophylla ). Mycopsylla proxima, the only other species reported from Australia, feeds on F. rubiginosa without any recorded outbreaks. We searched for homotomids and their parasitoids on eight Ficus species on the east coast of Australia, Lord Howe Island (LHI), and in Auckland, New Zealand, and detected them on three Ficus species. Using mitochondrial and nuclear DNA sequences, we delimited three Mycopsylla species, including a putative new species on F. watkinsiana . We also characterised six (including one previously described) parasitoid species of the genus Psyllaephagus (Hymenoptera: Encyrtidae) based on congruent morphological characters and molecular data. Each of the homotomid species was highly host specific to a single fig species, whereas parasitoid species varied in host specificity: three host specific to M. fici and three host generalists. Geographic distribution varied among parasitoid species; e.g. one host‐specific species was found on both the mainland and LHI, but a second species only on LHI. Our study revealed previously unrecognised diversity in fig homotomids and especially in their parasitoids. The herbivores and parasitoids showed contrasting patterns of host specificity. Interestingly, M. fici, the only outbreak species, had the highest diversity of associated parasitoid species and was the only species with host‐specific parasitoids.